Preparation, characterization and antimicrobial properties of electrospun polylactide films containing Allium ursinum L. extract. (September 2019) - Radusin, Tanja; Torres-Giner, Sergio; Stupar, Alena; Ristic, Ivan; Miletic, Aleksandra; Novakovic, Aleksandra; Lagaron, Jose Maria
Graphical abstract: Highlights: Allium ursinum L. (AU) extract was encapsulated by electrospinning in polylactide. AU extract was thermally stable and protected in the biopolymer matrix. Addition of extract improved water vapor barrier performance. Antimicrobial activity against E. coli and S. aureus bacteria was found. Electrospinning can be used for the preparation of active food packaging films. Abstract: Novel active films of polylactide (PLA) containing extract of Allium ursinum L. (AU), also called wild garlic, at 10 wt% were succesfully prepared by the electrospinning technology. Electrospinning of the AU-containing PLA solutions yielded fibers in the 1–2 μm range with a beaded-like morphology, suggesting that the AU extract was mainly encapsulated in certain fiber regions. The resultant electrospun mats were then subjected to annealing at 135 °C to obtain continuous films of application interest in active packaging. The film cross-sections revealed that the AU extract was incorporated into the PLA matrix in the form of micro-sized droplets. The thermal properties showed that the AU extract addition plasticized the PLA matrix and also lowered its crystallinity degree as it disrupted the ordering of the PLA chains by hindering their folding into the crystalline lattice. Thermal stability analysis indicated that the natural extract positively contributed to a delay in thermal degradation of the biopolymer and it was thermally stable when encapsulated in the PLA film. The AU extract incorporation also produced a mechanical reinforcement on the electrospun PLA films and improved slightly the water barrier performance. Finally, a significant antimicrobial activity of the electrospun PLA films containing the natural extract was achieved against foodborne bacteria.